2018
DOI: 10.1111/hex.12856
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of telephone outreach to enhance uptake of NHS Health Checks in more deprived communities and minority ethnic groups: A qualitative interview study

Abstract: Background The NHS Health Checks preventative programme aims to reduce cardiovascular morbidity across England. To improve equity in uptake, telephone outreach was developed in Bristol, involving community workers telephoning patients amongst communities potentially at higher risk of cardiovascular disease and/or less likely to take up a written invitation, to engage them with NHS Health Checks. Where possible, caller cultural background/main language is matched with that of the patient called. The call includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Brangan, Stone, Chappell, Harrison, and Horwood [21] reported on a telephone outreach intervention conducted to enhance the UK National Health Service (NHS) Health Check program, which provides cardiovascular risk assessment across England every five years for individuals who have not been diagnosed with the disease. In this program, those community workers were used who were almost identical to the study participants' cultural background and language.…”
Section: For Increasing Health Screening Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Brangan, Stone, Chappell, Harrison, and Horwood [21] reported on a telephone outreach intervention conducted to enhance the UK National Health Service (NHS) Health Check program, which provides cardiovascular risk assessment across England every five years for individuals who have not been diagnosed with the disease. In this program, those community workers were used who were almost identical to the study participants' cultural background and language.…”
Section: For Increasing Health Screening Compliancementioning
confidence: 99%
“…For instance, the outreach staff of a street outreach program went to certain places, such as streets, night clubs and buses, to meet the target audience of young male adults to educate them on sexually transmitted disease prevention methods [35]. Telephonic outreach activities have been shown to enhance health checks [21], and mailing outreach activities to increase colorectal cancer screenings [18,19]. These methods were used to reach target populations wherever they were.…”
Section: Empirical Referentsmentioning
confidence: 99%
“…Due to these activities, the rate of mammogram screening completion increased from 35% in 2010 to 72% in 2014 [18]. E Brangan, TJ Stone, A Chappell, V Harrison and J Horwood [19] reported on a telephone outreach intervention conducted to enhance the UK National Health Service(NHS) Health Check program, which provides cardiovascular risk assessment across England every 5 years to individuals who have not been diagnosed with the disease. It successfully engaged a population with higher health needs and reduced health inequalities in the city of Bristol, the most deprived area.…”
Section: For Increasing Health Screening Compliancementioning
confidence: 99%
“…These antecedents are necessary for the occurrence of community health outreach: Several studies [8][9][10][15][16][17][18][19][20][21][22] showed that community outreach has resulted in increasing levels of public health screenings and accessibility. Other studies [9,[23][24][25][26][27][28][29][30]…”
Section: Identifying Antecedents and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation